Nutritional characterization of Larrea divaricata Cav during winter and its potential as cattle and goats feed - Ramirez, María Rosana; Oyhenart, Jorge A.; Mohamad, Leandro; Rintoul, Ignacio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The ever-increasing global demand for agricultural commodities and progressive climate change factors are displacing extensive beef cattle and goat ranching from temperate humid regions to peripheral regions with semi-arid characteristics. Extensive investigation is required on native desert plants to be safely incorporated into feed programs and to maintain the biodiversity and sustainability of these fragile ecosystems. Larrea divaricata is a native plant adapted to arid and semi-arid biomes of South and Western-South America. This research evaluates the nutritional composition of the browsing available canopy parts of Larrea divaricata during the winter season in a semi-arid region of Argentina. Its crude protein content resulted in 11.20% of dried matter and its soluble protein content resulted in nearly 80% of the crude protein. Acid detergent fiber fraction, ash-corrected neutral detergent fiber fraction, lignin, ash content, fat-like compounds, and non-fibrous carbohydrates resulted in 17.42, 35.51, 12.09, 9.96, 5.92 and 3.82% of dried matter, respectively. Essential bioelements Ca, Mg and K resulted within standard forage requirements. Total polyphenols and flavonoids resulted in 430 mg/g and 140 mg/g, respectively. These results demonstrate that Larrea divaricata can be an effective complement for winter-feeding beef cattle and goats in arid and semi-arid regions. Highlights: Larrea divaricatacan be an effective complement for winter-feeding beef cattle and goats in arid and semi-arid regions. Crude protein and carbohydrates resulted in 11.20% and 9.74% of dried matter, respectively. Essential bioelements resulted within standard forage requirements.